147:oral Prioritisation in the United Kingdon national health service during a national emergency: a qualitative case study of surgical teams' experiences of colorectal cancer surgery in the acute early stages of the COVID-19 pandemic. (28th April 2022) - Conefrey, Carmel; Rooshenas, Leila; Main, Barry; Avery, Kerry; Bennett, Jo; Blazeby, Jane; Blencowe, Natalie; Elliott, Daisy; Ochieng, Cynthia; Hoffman, Christin; Jepson, Marcus; Kinross, James; et al.
Abstract : Introduction: The onset of the COVID-19 pandemic in early 2020 triggered reorganisation of hospital departments around the world as resources were configured to prioritise critical care. In spring 2020, NHS England issued national guidance proposing acceptable time intervals for postponing different types of surgical procedures for patients with cancer and other conditions. The 'Consider-19' study sought to investigate prioritisation decisions in practice, with in-depth examination of colorectal cancer surgery as a case-study, given recommendations that these procedures could be delayed by up to 12 weeks. Methods: Twenty-seven semi-structured interviews were conducted with healthcare professionals between June – November 2020. A key informant sampling approach was used, followed by snowballing to achieve maximum regional variation across the UK. Data were analysed thematically using the constant comparison approach. Results: Interviewees reported a spectrum of perceived disruption to colorectal cancer surgery services in the early phase of the pandemic, with some services reporting greater scarcity of resources than others. Nonetheless, all reported a need to prioritise patients based on local judgments. Prioritisation was framed by many as unfamiliar territory, requiring significant deliberation and emotional effort. Whilst national guidance provided a framework for prioritising, it was largely left to local teams to devise processes for prioritising within surgical specialities and then between different specialities, resulting in much local variation in practice. Discussion: The pandemic necessitated a significant change in practice as surgeons, in a tense and uncertain situation, found themselves having to navigate clinically, emotionally, and ethically-charged decisions about how best to use limited surgical resources. Whilst unavoidable, many felt uncomfortable with the task and the consequences for their patients. The findings point to a need to better support surgeons tasked with prioritising patients and raise questions about who should be involved in this activity.